Effective management of attention-deficit/hyperactivity disorder (ADHD) through structured re-assessment: the Dundee ADHD Clinical Care Pathway. Issue 1 (December 2015) - Coghill, David; Seth, Sarah
Abstract Attention-deficit/hyperactivity disorder (ADHD) has become a major aspect of the work of child and adolescent psychiatrists and paediatricians in the UK. In Scotland, Child and Adolescent Mental Health Services were required to address an increase in referral rates and changes in evidence-based medicine and guidelines without additional funding. In response to this, clinicians in Dundee have, over the past 15 years, pioneered the use of integrated psychiatric, paediatric, nursing, occupational therapy, dietetic and psychological care with the development of a clearly structured, evidence-based assessment and treatment pathway to provide effective therapy for children and adolescents with ADHD. The Dundee ADHD Clinical Care Pathway (DACCP) uses standard protocols for assessment, titration and routine monitoring of clinical care and treatment outcomes, with much of the clinical work being nurse led. The DACCP has received international attention and has been used as a template for service development in many countries. This review describes the four key stages of the clinical care pathway (referral and pre-assessment; assessment, diagnosis and treatment planning; initiating treatment; and continuing care) and discusses translation of the DACCP into other healthcare systems. Tools for healthcare professionals to use or adapt according to their own clinical settings are also provided.